Midterm Outcomes From a Pilot Study of Percutaneous Deep Vein Arterialization for the Treatment of No-Option Critical Limb Ischemia. (October 2017) - Kum, Steven; Tan, Yih Kai; Schreve, Michiel A.; Ferraresi, Roberto; Varcoe, Ramon L.; Schmidt, Andrej; Scheinert, Dierk; Mustapha, Jihad A.; Lim, Darryl M.; Ho, Derek; Tang, Tjun Y.; Alexandrescu, Vlad-Adrian; et al.
Purpose: To report the initial clinical experience with percutaneous deep vein arterialization (PDVA) to treat critical limb ischemia (CLI) via the creation of an arteriovenous fistula.Methods: Seven patients (median age 85 years; 5 women) with CLI and no traditional endovascular or surgical revascularization options (no-option CLI) were recruited in a pilot study to determine the safety of PDVA. All patients were diabetic; 4 had Rutherford category 6 ischemia. Six were classified at high risk of amputation based on the Society for Vascular Surgery WIfI (wound, ischemia, and foot infection) classification. The primary safety endpoints were major adverse limb events and major adverse coronary events through 30 days and serious adverse events through 6 months. Secondary objectives included clinical efficacy based on outcome measures including thermal measurement, transcutaneous partial pressure of oxygen (TcPO2 ), clinical improvement at 6 months, and wound healing.Results: The primary safety endpoints were achieved in 100% of patients, with no deaths, above-the-ankle amputations, or major reinterventions at 30 days. The technical success rate was 100%. Two myocardial infarctions occurred within 30 days, each with minor clinical consequences. All patients demonstrated symptomatic improvement with formation of granulation tissue, resolution of rest pain, or both. Complete wound healing was achieved in 4 of 7 patients and 5 of 7 patients at 6 and 12 months, respectively, with a median healing time of 4.6 months (95% confidence interval 84–192). Median postprocedure peak TcPO2 was 61 mm Hg compared to a preprocedure level of 8 mm Hg (p=0.046). At the time of wound healing, 4 of 5 of patients achieved TcPO2 levels of >40 mm Hg. There were 2 major amputations, 1 above the knee after PDVA thrombosis and 1 below the knee for infection. Three patients died of causes unrelated to the procedure or study device at 6, 7, and 8 months, respectively. Limb salvage was 71% at 12 months.Conclusion: PDVA is an innovative approach for treating no-option CLI and represents an alternative option for the "desert foot, " potentially avoiding major amputation. Our results demonstrate its safety and feasibility, with promising early clinical results in this small cohort.